EVALUASI KINERJA SABO DAM SUNGAI WAIPIAH KABUPATEN MALUKU - Henny Soplantila; Renny Betaubun; Penina Istia (Jurusan Teknik Sipil, 2023)
Sabo is a dam building with a roller built to prevent the dangers of floods and lava. Sabo Dam has enormous benefits. As a controller of forest erosion and agricultural areas and prevent the dangers of landslides. Sand materials and rocks stuck in Sabo can also be used by the community as a source of income, the problem is whether the condition of physical facilities. In this writing is a quantitative analysis method/ technique, where the data that needs to be calculated using the evaluation of the impact of damage to the Sabo Dam Dam Wai Pia building, evaluating water levels on sabo dam and evaluating sedimentation in sabo dams, the condition of flooding fluctuations in floods can Affecting the condition of Sabo Dam, and whether the sediment arising in the Sabo Dam shelter affects the height of the water level in Sabo Dam. With the aim of writing to know The results of the analysis are based on the results of the Sabo Dam performance and performance evaluation of the condition of the building is used to calculate the total score of the inspection results, the total item of the building condition, the total number of the largest score and the total score of the entire item and the level of damage in percent (%), the maintenance recommendations are determined based on the parameters and good conditions , if the damage rate is still below 10% of the initial construction conditions, the condition is slightly damaged, if the damage rate is 10% to below 20% of the initial conditions